CERTAIN ASPECTS REGARDING THE PARTIES’ AGREEMENT IN CIVIL PROCEDURE - Nicolae-Horia ȚIȚ (Challenges of the Knowledge Society, 2021)
The article examines how the agreement of the parties' may be relevant at various stages of the procedure, during the civil process. The provisions of the Romanian Code of Civil Procedure are analyzed in relation to the Model European Rules of Civil Procedure developed by the European Law Institute and UNIDROIT. Specifically, two situations in which the agreement of the parties takes effect in the procedural plan are herein being analyzed: (i) the establishment of the legal qualification concerning the acts and facts brought before in court and (ii) the agreement that may intervene in connection with certain aspects of evidence (their request after the deadline provided by the law, the conventions on evidence). The relationship between the principle of the judge's role in finding the truth and the principle of availability is being examined. The limits within which the parties may dispose by way of their agreement in the analyzed situations and the way in which the judge must relate to this manifestation of the principle of availability are also being further examined. The analysis intends to highlight the components of these principles and the development of a concept which targets the cooperation of the parties during the civil process is being proposed, highlighting the role of lawyers in identifying and applying appropriate procedural means for the court to resolve the matters that concern, in fact, the dispute between the parties.